Altered Tuber Yield in Genetically Modified High-Amylose and Oil Potato Lines Is Associated With Changed Whole-Plant Nitrogen Economy - Pourazari, Fereshteh; Andersson, Mariette; Weih, Martin (Frontiers in Plant Science, 2018)
Breeding for improved crop quality traits can affect non-target traits related to growth and resource use, and these effects may vary in different cultivation conditions (e.g. greenhouse vs. field). The objectives of this study are to investigate the growth and whole-plant nitrogen (N) economy of two genetically modified (GM) potato lines compared to their non-GM parental varieties and when grown in different cultivation conditions. A high-amylose GM potato line and its parent were grown under field and greenhouse conditions for one growing season in Sweden; and a GM oil potato line and its parent were grown in greenhouse conditions only. Tuber yield, above ground biomass, N uptake efficiency and other plant N economy traits were assessed. In both cultivation conditions, the GM lines produced between 1.5 and two times more tubers as compared with their parents. In the greenhouse, fresh tuber yield and N uptake efficiency were unaffected by the genetic modifications, but the GM-lines produced less tuber biomass per plant-internal N compared to their parents. In the field, the fresh tuber yield was 40% greater in the high-amylose line as compared with its parent; the greater fresh tuber yield in the high-amylose GM line was accomplished by higher water allocation to the harvested tubers, and associated with increased N recovery from soil (+20%), N uptake efficiency (+53%), tuber N content (+20%) and N accumulation (+120%) compared with the non-GM parent. The cultivation conditions influenced the yield and N economy. For example, the final fresh above-ground plant biomass and N pool were considerably higher in the greenhouse conditions, whilst the tuber yield was higher in the field conditions. In conclusion, the genetic modification inducing high accumulation of amylose in potato tubers affected several non-target traits related to plant N economy, and increased the plant N uptake and accumulation efficiency of the field-grown plants. Due to strongly increased plant N accumulation compared to the parental variety, the cultivation of the high-amylose line is expected to require higher N fertilization rates. However, starch productivity per unit land area or soil N still is expected to be higher in the high-amylose line.